Active site structure and absorption spectrum of channelrhodopsin-2 wild-type and C128T mutant. Issue 6 (8th March 2016) - Guo, Yanan; Beyle, Franziska E.; Bold, Beatrix M.; Watanabe, Hiroshi C.; Koslowski, Axel; Thiel, Walter; Hegemann, Peter; Marazzi, Marco; Elstner, Marcus
Abstract : We show by extensive ground state and absorption spectra simulations that the channelrhodopsin-2 active site samples three different hydrogen-bonding patterns. Abstract : In spite of considerable interest, the active site of channelrhodopsin still lacks a detailed atomistic description, the understanding of which could strongly enhance the development of novel optogenetics tools. We present a computational study combining different state-of-the-art techniques, including hybrid quantum mechanics/molecular mechanics schemes and high-level quantum chemical methods, to properly describe the hydrogen-bonding pattern between the retinal chromophore and its counterions in channelrhodopsin-2 Wild-Type and C128T mutant. Especially, we show by extensive ground state dynamics that the active site, containing a glutamic acid (E123) and a water molecule, is highly dynamic, sampling three different hydrogen-bonding patterns. This results in a broad absorption spectrum that is representative of the different structural motifs found. A comparison with bacteriorhodopsin, characterized by a pentagonal hydrogen-bonded active site structure, elucidates their different absorption properties.